2017
DOI: 10.1002/2017ja024547
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Remote Observations of Intense Reconnection Effects by DMSP and MMS Spacecraft During a Storm Time Substorm

Abstract: During a magnetic storm on 23 June 2015, several very intense substorms took place, with signatures observed by multiple spacecraft including DMSP and Magnetospheric Multiscale (MMS). At the time of interest, DMSP F18 crossed inbound through a poleward expanding auroral bulge boundary at 23.5 h magnetic local time (MLT), while MMS was located duskward of 22 h MLT during an inward crossing of the expanding plasma sheet boundary. The two spacecraft observed a consistent set of signatures as they simultaneously c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 53 publications
16
28
2
Order By: Relevance
“…We have indeed confirmed that these electrons are originally accelerated near the EDR and experience no additional significant acceleration and drifting during their propagation to the probe (not shown). This is a typical feature of the first contact of reconnection signatures at the reconnection boundary at a location sufficiently far away from the X‐line as very recently observed by MMS at the near‐Earth PSBL (Varsani et al, ). The P4 probe observes similar signatures Δ t = 2Ω i −1 later than P3 (see the time difference between two vertical lines in Figures g–l).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…We have indeed confirmed that these electrons are originally accelerated near the EDR and experience no additional significant acceleration and drifting during their propagation to the probe (not shown). This is a typical feature of the first contact of reconnection signatures at the reconnection boundary at a location sufficiently far away from the X‐line as very recently observed by MMS at the near‐Earth PSBL (Varsani et al, ). The P4 probe observes similar signatures Δ t = 2Ω i −1 later than P3 (see the time difference between two vertical lines in Figures g–l).…”
Section: Resultssupporting
confidence: 70%
“…After the first contact of the highest energy electrons, the lower energy electrons are sequentially observed and form the energy dispersion (see the time after the first vertical line in Figure g). This dispersion is caused mainly by the time‐of‐flight effect in which slower electrons reach the probe later than the faster electrons when these electrons are coming from a close location near the X‐line along the same field line and experience almost no additional acceleration during their flights (Varsani et al, ). We have indeed confirmed that these electrons are originally accelerated near the EDR and experience no additional significant acceleration and drifting during their propagation to the probe (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the time shown in Figure 2, MMS spent in the southern lobe as indicated by recordings of~100-eV polar rain electrons (Figure 2c) and by a spectacular trace of the cold ions in Figure 2a showing the lobe population, which is known from previous studies (e.g., Varsani et al, 2017). As in those previous papers, at the top of spectrogram (a) we overplotted the trace of kinetic energy due to the proton convective transport (Ep = m p VE 2 /2, VE = (E × B)/B 2 ).…”
Section: Observationssupporting
confidence: 66%
“…These flows are earthward at THEMIS and tailward at ARTEMIS, that is, magnetic reconnection occurs somewhere between the spacecraft positions (presumably around ∼30 R E , where the reconnection occurrence rate is highest; see Genestreti et al, ; Nagai et al, ). Because the THEMIS spacecraft are some distance from the equatorial plane (| B x | is large; see panels b1–b3), the significant part of the observed plasma flows is field‐aligned and can be attributed to the parallel propagating ions accelerated in the reconnection region (e.g., Nakamura et al, ; Varsani et al, ), whereas plasma flows observed by ARTEMIS are mostly transverse (i.e., these are typical reconnection tailward ejecta; see Kiehas et al, ; Runov et al, , and references therein). Thus, spacecraft (THEMIS and ARTEMIS) are located at different regions (not only different sides) of the middle‐tail reconnection.…”
Section: Spatial Localizationmentioning
confidence: 99%